La seguridad regional : hacia la consolidación de la zona desnuclearizada - Armanet Armanet, Pilar (Estudios Internacionales, 1984)
Latin America is the only inhabited area on the planet that has become a denuclearized region. The Treaty of Tlatelolco obliges the Latin American States to keep their territory completely free of nuclear weapons and is accompanied by two Protocols aimed at making the agreement effective. Although there are some ambiguities, weaknesses and difficulties in its implementation and its control mechanisms, after almost two decades of application in a continent marked by political instability, territorial conflicts and the ineffectiveness of economic cooperation mechanisms, it has managed to maintain to the region free of nuclear weapons and consequently much safer.